KINERJA BKKBN PADA PROGRAM KELUARGA BERENCANA DI KECAMATAN KOTAMOBAGU BARAT - NAYOAN, CINDY; LENGKONG, FLORENCE DAICY; TULUSAN, FEMMY (JURNAL ADMINISTRASI PUBLIK, 2018)
BKKBN Performance on Family Planning Program in Kecamatan Kotamobagu Barat. The publication of city dwellers in 2017 is the continuation of the publication as the business of the Central Bureau of Statistics (BPS) of kotamobagu city, the western kotamobagu district to meet the needs of the population data for the city districts of kotamobagu, subdistrict kotamobagu west in 2015 consists of 6 urban villages. Based on the five performance measurement indicators according to Agus Dwiyanto (2002), in BKKBN it can be said that in general the performance of BKKBN is still less maximal, on indicator Service cost productivity, BKKBN does not charge to the public, because the budget used comes from APBN and APBD. Then on the indicators of the quality of the Service, the constraints are the ineffectiveness of BKKBN in reaching the places - places that are not within a certain range, due to the distance constraints experienced by extension workers. on the indicator of responsiveness where the existence of programs that do not run well like the program PUP (maturity age marriage), can be seen from the number of early marriage in the district of West Kotamobagu, is the impact of the lack of understanding of the community will the dangers of early marriage to maternal reproductive health young, not to mention the old understanding that is still firmly attached in the community district of West Kotamobagu. Indicator of responsibilities, with not running maximally program from BKKBN impact to society dissatisfaction.Keywords: Performance, BKKBN, Family Planning